"Permission to Speak": A Postcolonial View on Racialized Bodies and PE in the Current Context of Globalization. Issue 2 (2nd April 2016) - Azzarito, Laura
Abstract : The current neoliberal context of schools presents difficult challenges in addressing persistent issues of social inequalities. In this article, first, I argue that because of today's market-driven education, the rise of fitness testing in school physical education (PE) can be seriously detrimental to young people in general and to ethnic-minority young people's embodied identity in particular. Second, I explain how the racialization process circulated by the body-at-risk discourse, sustained by the media, and reproduced by high-stakes testing in PE forces ethnic-minority young people to construct their identities through White eyes, which alienates them from a consciousness of their own identity. Third, I explore the possible uses and pitfalls of Spivak's theoretical notion of "strategic essentialism" to put forward strategies to build a positive image of the "other" while attempting to avoid the erasure of difference. Fourth, I conclude the article by suggesting how Spivak's notion of strategic essentialism can be useful in rethinking current PE fitness practices.